ESTIMATION OF FISHERY RESOURCES BY SONAR SURVEYS - RAO, K KRISHNA; NATARAJAN, S; DANIEL, G.P EDWIN (Fishery Technology, 2017)
The methodology adopted by the Pelagic Fishery Project, Cochin for surveying the surface fish schools with sonar equipment, is described. The estimates of the biomass arrived at from the surveys conducted during 197 5-’78 are presented.